Design and fabrication multipurpose rack structure - Mohd Noor Hafiz, Ahmad (2009)
The use of rack was already about a long time ago which made it has a own history. The multipurpose rack structure had a objective to be design and fabrication the multipurpose rack structure with mechanical skill. Furthermore this rack has own rule specifications of safety to prevent like the other rack in market are higher risk to consumer which has a sharp edge. Made with major material is wood and combine of zinc and magnet. Portable which is others name can be bring anywhere because has ideal weight and comfortable holder. Beside a maximum load can put in content is a 5 kg. Anew design to rack has a magazine rack and clock structure. It also has a high stability because of the design very good to multipurpose rack structure. A little drawer which can put some small thing to prevent from broke. A few recommendations and work progress had be written in this report.